The Art of Strategic Leadership : How Leaders At All Levels Prepare Themselves, Their Teams, and Organizations for the Future - Stowell, Steven J. and Mead, Stephanie S. (New Jersey Wiley, 2016)
Develop the qualities of strategic leadership and become an active contributor to the short- and long-term success of your organization Today's organizations face two daunting challenges: 1. How to create new sources of competitive advantage to sustain long-term growth, and 2. How to engage leaders at every level of the organization so that they are more proactive and forward-looking in their area of responsibility. The Art of Strategic Leadership uses a unique approach to examine what it means to be a strategic leader. Instead of focusing on the skills, behaviors, and tools found in typical books on strategic leadership, the authors shed light on the attributes and qualities necessary to lead strategic change and help transform a business. Strategic leadership is what modern leadership is all about. Organizations expect leaders to anticipate and be proactive more than ever before. In this book, the authors draw on their vast experience working directly with leaders at all levels and use an intriguing narrative to explain this inside-out approach to understanding strategic leadership. The narrative follows the journey of how one manager discovered these critically important qualities. You will experience first-hand how these values and attributes manifest in the lives of realistic leaders; how they orchestrate long-term strategic change needed for the organization to compete and survive and actively shape the future while delivering short-term results. The Art of Strategic Leadership provides the content that will help you informally assess and reflect on your own strategic leadership qualities-those that are strengths and those that indicate areas you need to develop. It will guide you as you incorporate these values and qualities into your own leadership style and become a more effective catalyst for change. This book will help you in the following ways: Develop a more proactive, forward-thinking approach to leadership Approach strategy from both short- and long-term perspectives Adopt the core values and principles of a strategic leader Model the qualities exhibited by powerful leaders Strategic leaders serve as powerful examples to others in the organization. Their qualities and traits spread rapidly to those around them, empowering people at every level to take a more active role in meeting the demands of the future. The Art of Strategic Leadership will help you deepen and broaden your understanding of the core qualities of strategic lead
Include Index
Keywords: Strategic planning -- Leadership